Solution of the Applied Task to Determine Total Exposure for Mechanical Engineering Workers; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Medvedeva O. V. Olesya Vladimirovna (2016, 2016)
Title screen